The Determinant Factors of Nurse Compliance in the Use of Personal Protective Equipment (PPE) - Azwaldi, Azwaldi; Agustin, Ismar (JOSING: Journal of Nursing and Health, 2022)
This study aims to see the determinants associated with compliance with the use of PPE. The research design used is a cross-sectional study. The results showed differences in the average value of knowledge, attitudes, motivation, supervision, and PPE standards/guidelines between nurses who obeyed using PPE and those who did not comply with using PPE. In conclusion, multiple logistic regression analysis shows that knowledge is the most influential variable in nurses' compliance with the use of PPE. Keywords: Personal Protective Equipment, Compliance, Nursing Services, Nurse